New Turbidity Method to Determine of Calcium Ion in Pharmaceutical Preparations Samples - Shaymaa Ibrahim Saeed (Journal of Global Pharma Technology, 2018)
A new turbidity method was used to determination of calcium ion in the pharmaceutical preparation samples. The proposed method was supported reagent and sodium dodecyl sulfate (SDS) as anionic surfactant. The main factors affecting was study such as order addition effect, pH solution, concentration of reagent, concentration of surfactant, effect of equilibrium temperature and incubation time, effect of interferences. The calibration curve was linear in the range of 0.3-30.0 µg /ml with a correlation coefficient r2 = 0.9996 at pH 4.42. The relative standard deviation obtained 0.0656, and the limit of detection was 1.0 µg /ml. The method used in this research has been successfully utilized in the estimation of Ca (II) in pharmaceutical preparations samples.Keywords: Calcium ion, Turbidity, Cloud point extraction, Sodium dodecyl sulfate.